Relationship‐based assessments: The importance for early childhood mental health clinicians. Issue 6 (June 2016) - Gallagher, Jennifer
Abstract : Emma is a 4‐year‐old girl who was referred for outpatient treatment by her pediatrician due to reports of Emma's disruptive behaviors both at home and at school. Upon arrival to the outpatient clinic and while awaiting her initial appointment, Emma ran around the waiting room, knocked down another child's Lego creations, and growled at the receptionist. Despite her mother's best efforts, she was unable to effectively manage Emma's behaviors. During the initial appointment, Emma had great difficulty controlling her actions and was easily distracted. Emma's mother presented as disengaged and defeated. Emma's mother provided very little information about Emma's history throughout the session. She noted that Emma's father was a "terrible man" but they were now separated, and stated she did not want to talk about it when the clinician asked for further information.